Evaluation of the insertion torque, implant stability quotient and drilled hole quality for different drill design: an in vitro Investigation. Issue 6 (8th March 2016) - Gehrke, Sergio Alexandre; Guirado, José Luis Calvo; Bettach, Raphaël; Fabbro, Massimo Del; Martínez, Carlos Pérez‐Albacete; Shibli, Jamil Awad
Abstract: Objective: The purpose of the present study was to compare the insertion torque and implant stability quotient between different drill design for implant site preparation. Materials and Methods: Synthetic blocks of bone (type I density) were used for drilling procedures. Three groups were evaluated: Group G1 ‐ drilling with a single bur for a 4.2 mm conical implant; Group G2 and Group G3 ‐ drilling with three consecutive burs for a 4.1 mm cylindrical implant and for a 4.3 mm conical implant respectively. For each group, 15 drilling procedures were performed without irrigation for 10‐mm in‐depth. The drilled hole quality (HQ) after the osteotomy for implant site preparation was measured in the five‐first holes through a fully automated roundness/cylindricity instrument at three levels (top, middle, and bottom of the site). The insertion torque value (ITV) was achieved with a computed torquimeter and the implant stability quotient (ISQ) values were measured using a resonance frequency apparatus. Results: The single drill (group 1) achieved a significantly higher ITV and ISQ than the multiple drills for osteotomy (groups 2 and 3). Group 1 and 3 displayed significantly better HQ than group 2. Conclusions: Within the limitations of the study, the results suggest that the hole quality, in addition to the insertion torque, may significantly affect implant primary stability.